2018
DOI: 10.1093/ptj/pzy037
|View full text |Cite
|
Sign up to set email alerts
|

A Physical Therapist–Administered Physical Activity Intervention After Total Knee Replacement: Protocol for a Randomized Controlled Trial

Abstract: The goal of this randomized controlled trial is to increase PA after TKR. A protocol for investigating the efficacy, fidelity, and safety of a physical therapist-administered PA intervention for people after TKR is presented. The findings will be used to support a large multisite clinical trial to test the effectiveness, implementation, and cost of this intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…As for the PhD dissertation, the effort made to retrieve the full text through the University of Nottingham interlibrary loans services was not successful. Two other studies that are at the protocol stage were identified (27,28) No relevant unpublished studies were obtained. See flow diagram in Figure 1.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the PhD dissertation, the effort made to retrieve the full text through the University of Nottingham interlibrary loans services was not successful. Two other studies that are at the protocol stage were identified (27,28) No relevant unpublished studies were obtained. See flow diagram in Figure 1.…”
Section: Study Selectionmentioning
confidence: 99%
“…Future studies--such as high quality, large-scale, randomised, controlled trials--should consider addressing these issues. We have also identified two randomised, controlled trials (27,28) that are at the protocol stage which could add credence to the evidence regarding effective physical activity interventions. Full-text articles excluded, with reasons (n =2)…”
Section: Implication For Researchmentioning
confidence: 99%
“…The pain receptor transmits the pain signal to sensory neuron till the sensory centre of cerebral cortex and makes patients feel more painful [ 24 27 ]. The study of scholar Christiansen M showed that TKA can reduce the concentration of TNF- α and IL-1 β in patients, so as to reduce the inflammatory transmitter produced by chondrocytes, with less pain and better recovery effect of knee joints [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…e study of scholar Christiansen M showed that TKA can reduce the concentration of TNF-α and IL-1β in patients, so as to reduce the inflammatory transmitter produced by chondrocytes, with less pain and better recovery effect of knee joints [28].…”
Section: Discussionmentioning
confidence: 99%
“…Possible reasons are a lack of specific PA feedback by the treating physical therapists, and not using the accelerometers to help patients meet their daily PA requirements. Currently, a randomized controlled trial is running that investigates the effect of a weekly PA intervention in KA patients, including an accelerometer, individualized step goals, and face-to-face feedback provided by a physical therapist [30]. A prior pilot study already showed that the use of direct PA feedback in postoperative rehabilitation results in larger increases in PA after KA, which is important for better reaching health-enhancing PA levels [31,32].…”
Section: Discussionmentioning
confidence: 99%